Linguistic peculiarities of George Gordon Byron poetry (Literatures of the World: Poetics, Mentality and Spirituality, 2017)
In the article «The linguistic features of poetry Jorda Gordon Byron» raised the issue of translation of poems written by the master, inspired putushestviem the East. Translated to talk about comparative linguistic property of the spoken language and the target language from the source. Also, talk about J. made. G. Byron in the poem the words of Eastern origin and the ability of interpreters «East poem».
Keywords: oriental poems; translator; poetry; style; original; English romanticism